Genome-Wide Comprehensive Identification and In Silico Characterization of Lectin Receptor-Like Kinase Gene Family in Barley (Hordeum vulgare L.) - Fee Faysal Ahmed; Farah Sumaiya Dola; Md Shohel Ul Islam; Fatema Tuz Zohra; Nasrin Akter; Shaikh Mizanur Rahman; Md. Abdur Rauf Sarkar (Genetics Research)
Lectin receptor-like kinases (LecRLKs) are a significant subgroup of the receptor-like kinases (RLKs) protein family. They play crucial roles in plant growth, development, immune responses, signal transduction, and stress tolerance. However, the genome-wide identification and characterization of LecRLK genes and their regulatory elements have not been explored in a major cereal crop, barley (Hordeum vulgare L.). Therefore, in this study, integrated bioinformatics tools were used to identify and characterize the LecRLK gene family in barley. Based on the phylogenetic tree and domain organization, a total of 113 LecRLK genes were identified in the barley genome (referred to as HvlecRLK) corresponding to the LecRLK genes of Arabidopsis thaliana. These putative HvlecRLK genes were classified into three groups: 62 G-type LecRLKs, 1 C-type LecRLK, and 50 L-type LecRLKs. They were unevenly distributed across eight chromosomes, including one unknown chromosome, and were predominantly located in the plasma membrane (G-type HvlecRLK (96.8%), C-type HvlecRLK (100%), and L-type HvlecRLK (98%)). An analysis of motif composition and exon-intron configuration revealed remarkable homogeneity with the members of AtlecRLK. Notably, most of the HvlecRLKs (27 G-type, 43 L-type) have no intron, suggesting their rapid functionality. The Ka/Ks and syntenic analysis demonstrated that HvlecRLK gene pairs evolved through purifying selection and gene duplication was the major factor for the expansion of the HvlecRLK gene family. Exploration of gene ontology (GO) enrichment indicated that the identified HvlecRLK genes are associated with various cellular processes, metabolic pathways, defense mechanisms, kinase activity, catalytic activity, ion binding, and other essential pathways. The regulatory network analysis identified 29 transcription factor families (TFFs), with seven major TFFs including bZIP, C2H2, ERF, MIKC_MADS, MYB, NAC, and WRKY participating in the regulation of HvlecRLK gene functions. Most notably, eight TFFs were found to be linked to the promoter region of both L-type HvleckRLK64 and HvleckRLK86. The promoter cis-acting regulatory element (CARE) analysis of barley identified a total of 75 CARE motifs responsive to light responsiveness (LR), tissue-specific (TS), hormone responsiveness (HR), and stress responsiveness (SR). The maximum number of CAREs was identified in HvleckRLK11 (25 for LR), HvleckRLK69 (17 for TS), and HvleckRLK80 (12 for HR). Additionally, HvleckRLK14, HvleckRLK16, HvleckRLK33, HvleckRLK50, HvleckRLK52, HvleckRLK56, and HvleckRLK110 were predicted to exhibit higher responses in stress conditions. In addition, 46 putative miRNAs were predicted to target 81 HvlecRLK genes and HvlecRLK13 was the most targeted gene by 8 different miRNAs. Protein-protein interaction analysis demonstrated higher functional similarities of 63 HvlecRLKs with 7 Arabidopsis STRING proteins. Our overall findings provide valuable information on the LecRLK gene family which might pave the way to advanced research on the functional mechanism of the candidate genes as well as to develop new barley cultivars in breeding programs.